Mauqif al-Nāsyitīn al-Islāmiyyīn fī Indonesiā - Tiar Anwar (Universitas Darussalam Gontor, 2020)
Since setlement of Jewish aprroved by Balfour Declaration in 1917, the Palestinian problem not only been the concern of the Chalif of Ustmani and the Arabic leader around Baitul-Maqdis. At the time, many leaders and poeple of Moslem in Indonesian country (yet: Hindia Belanda) gave attention to this problem as well as other Muslim around the Islamic world. They were involved with this complicated problem even if in the same situation colonialized for long time by the Dutch. This colonized situation not be an obstacle for the Indonesian Muslim activists to make many real actions for standing up with Baitul Maqdis and speaking up the liberation of Palestine from Jewish occupation. The aims of this paper are to know: (1) the standpoint of the Indonesian Islamic activist for Baitul-Maqdis issues? and (2) what they did to make action to deal with this issues? To answer this questions, I plan to search the otentic historical resourches in the magazines and newspapers were issued between 1917 to 1948 by the Islamic movement as well as Sarekat Islam (SI), Muhammadiyah, Nahdhatul Ulama (NU), Persatuan Islam (Persis), and many others. This resourches will be analized by the historical method to result the naration about what asked above. By pre-analysis, the informations that many times Indonesian Islamic activist held the event to support Baitul-Maqdis were found up in several books and journals. For the instance at July 5th 1937 held the big conference in Surabaya. In this conference, Palestinian Comittee’s formed. This comittee’s chaired by Wondoamiseno from Sarekat Islam (SI). The chairpersons form many others movement such as KH. Mas Mansur (Muhammadiyah), KH. Abdoel Wachab (NU), Sayyid Noeh Al-Kaff (Habaib), Oemar Hoebeis (Al-Irsyad). K.H. Kahar Muzakkir (Sarekat Islam), and others came and gave the speeches for this conference. This event can be first sign for us to search other fact that will reach this paper’s questions.